DNA Repair Protocols - Henderson, Daryl S.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2006)
In this second edition of a much praised laboratory manual devoted to eukaryotic systems, Daryl S. Henderson has refocused the book on mammalian cells, adding fourteen entirely new chapters and extensively revising many of the remaining chapters. The authors address a broad range of questions about practical mammalian DNA repair, including such arcana as "what is radioresistant DNA synthesis and how is it measured?" The techniques presented are readily reproducible and offer cutting-edge methods for cytogenetic analysis, measuring the cellular response to ionizing radiation, detecting single-strand (nicks) and double-strand DNA breaks, detecting the presence of "adducted" bases in DNA, and preparing mismatch repair (MMR) plasmid substrates. Among the highlights are excellent coverage of both base excision repair (BER) and nucleotide excision repair (NER), useful assays for identifying and quantifying UV-induced DNA lesions and DNA breakage, gene therapy, environmental mutagenesis and cancer, and gene targeting. The protocols follow the successful Methods in Molecular Biology™ series format, each offering step-by-step laboratory instructions, an introduction outlining the principles behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Authoritative and highly practical, DNA Repair Protocols: Mammalian Systems, Second Edition, offers investigators a wide variety of productive methods to explore and make new discoveries in the world of mammalian DNA repair.
Isolation of Mutagen-Sensitive Chinese Hamster Cell Lines by Replica Plating -- Complementation Assays Adapted for DNA Repair-Deficient Keratinocytes -- Cytogenetic Challenge Assays for Assessment of DNA Repair Capacities -- Evaluating the Delayed Effects of Cellular Exposure to Ionizing Radiation -- Inhibition of DNA Synthesis by Ionizing Radiation -- Analysis of Inhibition of DNA Replication in Irradiated Cells Using the SV40-Based In Vitro Assay of DNA Replication -- Cytometric Assessment of Histone H2AX Phosphorylation -- Detection of DNA Strand Breaks by Flow and Laser Scanning Cytometry in Studies of Apoptosis and Cell Proliferation (DNA Replication) -- In Vitro Rejoining of Double-Strand Breaks in Genomic DNA -- Detection of DNA Double-Strand Breaks and Chromosome Translocations Using Ligation-Mediated PCR and Inverse PCR -- Plasmid-Based Assays for DNA End-Joining In Vitro -- Use of Gene Targeting to Study Recombination in Mammalian Cell DNA Repair Mutants -- Gene-Specific and Mitochondrial Repair of Oxidative DNA Damage -- Quantitative PCR-Based Measurement of Nuclear and Mitochondrial DNA Damage and Repair in Mammalian Cells -- Measuring the Formation and Repair of DNA Damage by Ligation-Mediated PCR -- Immunochemical Detection of UV-Induced DNA Damage and Repair -- A Dot-Blot Immunoassay for Measuring Repair of Ultraviolet Photoproducts -- Quantification of Photoproducts in Mammalian Cell DNA Using Radioimmunoassay -- DNA Damage Quantitation by Alkaline Gel Electrophoresis -- The Comet Assay -- Fast Micromethod DNA Single-Strand-Break Assay -- 32P-Postlabeling DNA Damage Assays -- Electrophoretic Mobility Shift Assays to Study Protein Binding to Damaged DNA -- Construction of MMR Plasmid Substrates and Analysis of MMR Error Correction and Excision -- Characterization of Enzymes That Initiate Base Excision Repair at Abasic Sites -- Base Excision Repair in Mammalian Cells -- In Vitro Base Excision Repair Assay Using Mammalian Cell Extracts -- Biochemical Assays for the Characterization of DNA Helicases -- Repair Synthesis Assay for Nucleotide Excision Repair Activity Using Fractionated Cell Extracts and UV-Damaged Plasmid DNA -- Assaying for the Dual Incisions of Nucleotide Excision Repair Using DNA with a Lesion at a Specific Site -- Analysis of Proliferating Cell Nuclear Antigen (PCNA) Associated With DNA Excision Repair Sites in Mammalian Cells -- Analysis of DNA Repair and Chromatin Assembly In Vitro Using Immobilized Damaged DNA Substrates.
Keywords: Biochemistry; Cell biology; Biochemistry, general; Cell Biology